2021
DOI: 10.1159/000518670
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Aortic Calcification in Stage 4–5 Chronic Kidney Disease Patients Transitioning to Dialysis and Transplantation

Abstract: <b><i>Background and Aims:</i></b> Abdominal aortic calcification (AAC) is common in chronic kidney disease (CKD) patients and associated with increased mortality. Comparative data on the AAC score progression in CKD patients transitioning from conservative treatment to different modalities of renal replacement therapy (RRT) are lacking and were examined. <b><i>Methods:</i></b> 150 study patients underwent lateral lumbar radiograph to study AAC in the beginning o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Several other studies reported repeatability metrics for the SV score (see Table 3 for a brief review). Still, no other indicators are usually available than ICC, or concordance statistics on patient classification according to a threshold [ 17 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Our inter-operator ICC results for the SV score are generally lower than other studies: in the first repetition the ICC we report (0.65) is similar only to that of Toussaint et al [ 28 ], which, however, stands out from all other reports.…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies reported repeatability metrics for the SV score (see Table 3 for a brief review). Still, no other indicators are usually available than ICC, or concordance statistics on patient classification according to a threshold [ 17 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Our inter-operator ICC results for the SV score are generally lower than other studies: in the first repetition the ICC we report (0.65) is similar only to that of Toussaint et al [ 28 ], which, however, stands out from all other reports.…”
Section: Discussionmentioning
confidence: 99%
“…However, DXA does not differentiate between cortical and trabecular bone [34,46] nor between deficit in bone volume and mineralisation [46]. DXA data may be limited and confounded by calcification of the abdominal aorta [46], which is a common complication of CKD and kidney failure [50,51]. The 2009 KDIGO Clinical Practice Guideline for the Care of Kidney Transplant Recipients suggested that patients with estimated glomerular filtration rate (eGFR) > 30 mL/min/1.73 m 2 should have their bone mineral density measured in the first 3 months after kidney transplantation, if they receive corticosteroids or have risk factors for osteoporosis, as in the general population.…”
Section: Dxamentioning
confidence: 99%